Pengembangan SI-BELBI sebagai Media Pembelajaran Digital Interaktif pada Pembelajaran PAI di SD Kelas IV - Asyifa, Firdaus Musaddad; Khaerani, Fitria; Patmawati, Pina; Nurhayati, Sri Ai; Aeni, Ani Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to develop an interactive digital learning media, SI-BELBI (Islamic Cultural Learning System), for Islamic Religious Education (PAI) learning in fourth grade elementary schools. This research is based on the limitations of learning media that can integrate cultural values and Islamic teachings in an interesting, contextual, and appropriate manner to student characteristics. This study uses a Research and Development (R&D) methodology with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects included fourth grade students, teachers, and material and media experts. Data collection techniques were carried out through interviews, observations, questionnaires, and documentation, while data analysis included quantitative descriptive methods. The study showed that the SI-BELBI media has a high level of feasibility, with validation from material experts of 87.5% and media experts of 97.5%, so it is categorized as feasible to very feasible. In addition, student responses showed a very high level of practicality and engagement (95%). This media has been proven to be able to increase learning motivation, facilitate understanding of Islamic cultural concepts, and create an interactive and enjoyable learning experience. Therefore, SI-BELBI is worthy of being used as an innovation in digital learning media based on values in Islamic religious education in elementary schools.